2021
DOI: 10.3389/fmicb.2021.614058
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Carbapenemase Genes in Pseudomonas aeruginosa

Abstract: Carbapenem-resistant Pseudomonas aeruginosa is one of the major concerns in clinical settings impelling a great challenge to antimicrobial therapy for patients with infections caused by the pathogen. While membrane permeability, together with derepression of the intrinsic beta-lactamase gene, is the global prevailing mechanism of carbapenem resistance in P. aeruginosa, the acquired genes for carbapenemases need special attention because horizontal gene transfer through mobile genetic elements, such as integron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(161 citation statements)
references
References 209 publications
5
131
0
1
Order By: Relevance
“…Therefore, its prevalence is closely depending on geographic region, methods of testing and the major variability in application of infection control guidelines and antibiotic stewardships, which affect spread of resistant strains. 24 Minimum inhibitory concentration of meropenem in 84% of the isolates was more than 128g/ml in this study; reflecting high resistance in these isolates. This finding was in accordance with a study which revealed high level of meropenem resistance (MIC > 64 µg/ml), which was allied to multiple mechanisms including carbapenemase production and efflux-pump overexpression.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, its prevalence is closely depending on geographic region, methods of testing and the major variability in application of infection control guidelines and antibiotic stewardships, which affect spread of resistant strains. 24 Minimum inhibitory concentration of meropenem in 84% of the isolates was more than 128g/ml in this study; reflecting high resistance in these isolates. This finding was in accordance with a study which revealed high level of meropenem resistance (MIC > 64 µg/ml), which was allied to multiple mechanisms including carbapenemase production and efflux-pump overexpression.…”
Section: Discussionmentioning
confidence: 55%
“…As acquisition of carbapenemases is considered to be of high epidemiological concern in the growing resistance to carbapenems [14], 32 carbapenem-resistant isolates from our previous study [23] were screened for common carbapenemase genes (Table 1) using conventional end-point PCR.…”
Section: Detection Of Carbapenemase Genes In Resistant P Aeruginosa Isolatesmentioning
confidence: 99%
“…Resistance to carbapenems in P. aeruginosa can occur through three major mechanisms: acquisition of carbapenemases (carbapenem-hydrolyzing enzymes), which hydrolyze the β-lactam ring directly; overexpression of drug efflux pumps, such as those belonging to the resistance-nodulation-division (RND) family, which facilitate the export of carbapenems from the cell; and reduction in cell permeability through the downregulation or loss of OprD porins required for carbapenem entry [12,13]. Notably, the acquisition of carbapenemases is of great concern, as these can hydrolyze most β-lactam antibiotics and are encoded by genes carried on mobile genetic elements, which aid in the horizontal transfer of these genes to other bacterial species [6,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the MGE-related carbapenemase families that have been reported in P. aeruginosa include class A (KPC-2 [6] and GES [7]), class B (IMP [8], VIM [9], SPM [10], NDM [11], AIM [12], SIM [13], FIM [14], HMB [15], and CAM [16]), and class D (OXA-40-like [17], OXA-48-like [18], and OXA-198-like [19]). P. aeruginosa is the predominant host for class B enzymes, while class A and D enzymes are less commonly reported in this species [20].…”
Section: Introductionmentioning
confidence: 96%